Artificial Intelligence in Prenatal Ultrasound Diagnosis - He, Fujiao; Wang, Yaqin; Xiu, Yun; Zhang, Yixin; Chen, Lizhu (Frontiers in Medicine, 2021)
The application of artificial intelligence (AI) technology to medical imaging has resulted in great breakthroughs. Given the unique position of ultrasound (US) in prenatal screening, the research on AI in prenatal US has practical significance with its application to prenatal US diagnosis improving work efficiency, providing quantitative assessments, standardizing measurements, improving diagnostic accuracy, and automating image quality control. This review provides an overview of recent studies that have applied AI technology to prenatal US diagnosis and explains the challenges encountered in these applications.